Hazard assessment of chemicals : current developments. - Saxena, Jitendra (Academic Press, 1984)
Hazard Assessment of Chemicals: Current Developments, Volume 3 is a collection of expertly written articles that provide relevant and important information on the environmental and health hazard assessment of chemicals. The volume presents studies and expositions on such topics as hazard priority ranking system (or scoring system), a method to rank chemicals on the severity of their ill effects on the environment and human health. The book also tackles the effect of particulates on the toxic manifestations of chemicals; application of aquatic organisms as indicator systems for early detection.